Financial Crises: Review of Eichengreen and Tirole - Fischer, Stanley (Journal of Economic Literature, 2004)
This is a review article of two books: Financial Crises and What to Do about Them by Barry Eichengreen (Oxford University Press 2002) and Financial Crises, Liquidity, and the International Monetary System by Jean Tirole (Princeton University Press 2002).